Disparity Between E-Government and Human Resources in The Village - Sunardi Sunardi; Haryanto Haryanto; Nurlinah Nurlinah (JURNAL ILMU SOSIAL, 2019)
This paper examines technology-based governance (E-Government) and the impact of an information technology-based financial management system (hereinafter referred to as Siskeudes) in the village. Village Law No. 6 of 2014 has opened space for financial autonomy as well as encouraging technology-based financial management models (Siskeudes) in the village. The purpose of this study was to examine the impact of Siskeudes in Panaikang Village, Gowa Regency, South Sulawesi Province using qualitative research method. Data collection techniques were carried out through direct observation and interviews with village officials such as the village treasurer, the Siskeudes operator, and a village staff member. Furthermore, the results of the study were reduced, then described by linking several secondary data and field notes. The data obtained was finally presented as a result of the study. The results found that the Siskeudes triggered a disparity between technological developments and the availability of human resources in the village. The disparity referred to here is the unequal social gap. On the one hand, the development of E-Government in the village, especially the village governance went rapidly; while on the other hand, the capability and skills of human resources are still lagging.